Radiographic Factors Associated With Failure of Revision Hip Arthroscopy - David A. Bloom, B.A; Stephen W. Yu, M.D; Matthew T. Kingery, B.A; Nainisha Chintalapudi, B.S; Christopher Looze, M.D; Thomas Youm, M.D (Elsevier, 2021)
Purpose: To identify clinical and radiographic factors associated with failure of revision hip arthroscopy (RHA). Methods: A database was used to identify patients who underwent primary hip arthroscopy and revision hip arthroscopy (RHA) from January 2007 to December 2017 for the indication of femoroacetabular impingement and failure of the index procedure, respectively. The primary outcome was defined as the change, or difference, in the preoperative to postoperative alpha angle between patients with successful RHA and those with failed RHA. Failure was defined as reoperation on the operative hip for any indication or a modified Harris Hip Score (mHHS) of less than 70 at the 1-year postoperative time point. All patients had a minimum of 2 years' follow-up from the date of revision hip surgery. Patients with a history of revision were divided into those with failed revisions and those with successful revisions. The inclusion criteria for failed revision included a history of subsequent revision surgery (or arthroplasty) or an mHHS of less than 70 at final follow-up. Results: The study included 26 patients, comprising 8 (31%) with failed RHA and 18 (69%) with successful revision. The failure group showed a significantly smaller decrease in the alpha angle with surgery, measured on the Dunn view, compared with the success group. When the preoperative alpha angle was held constant, each 1° increase in the difference between the preoperative and postoperative alpha angles achieved during surgery was associated with a 17% decrease in the odds of failure. Patients included in the success group had both a higher preoperative mHHS (44.2 ± 8.6 vs 34.7 ± 9.6) and a higher postoperative mHHS (83.2 ± 8.3 vs 62.3 ± 14.2) than patients with failed RHA. There was a statistically significant difference in the frequency of patients who achieved the patient acceptable symptomatic state of +74.0 between the failure (25%) and success (83%) groups; 88% of patients in the failure group met the minimal clinically important difference, whereas 100% of patients in the success group (n = 18) met it. Conclusions: Complete resection of cam lesions as determined by changes in the alpha angle, anterior offset, and head-neck ratio when measured on the Dunn 45° view correlates with positive clinical outcomes after RHA. Level of Evidence: III, Retrospective Comparative Study.